Porta-enxertos na produção e nas características físico-químicas da uva e do vinho de diferentes cultivares em Jundiaí, SP - Silva, Marlon Jocimar Rodrigues da [UNESP] (2015)
The aim of this study was to evaluate the influence of rootstocks ‘IAC 766’ and ‘106-8 Mgt’ in the production characteristics, physical, chemical and biochemical of different cultivars of grapes for wine as well as the influence of the same rootstocks in physical and chemical characteristics of musts of red and white wines, and the levels of phenolic compounds and antioxidant activity of wines. The experiment was conducted in the experimental area of the Centro APTA de Frutas do Instituto Agronômico in Jundiaí-SP, Laboratory of Beverage, Department of Horticulture, FCA/UNESP and at the Laboratory of Postharvest the Biosciences Institute IBB/UNESP, Botucatu-SP, from August 2013 to December 2014. The treatments consisted of two rootstocks (‘IAC 766’ and ‘106-8 Mgt’) and 12 cultivars (‘Isabel’, ‘Bordô’, ‘Cabernet Sauvignon’, ‘Cabernet Franc’, ‘Merlot’, ‘Syrah’, ‘Sauvignon Blanc’, IAC 138-22 ‘Máximo’, IAC 116-31 ‘Rainha’, IAC 21-14 ‘Madalena’, ‘BRS Lorena’ ...